Analisis Faktor-Faktor Yang Mempengaruhi Konservatisme Akuntansi (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Riska Dwi Rizkyanti. Analysis of Factors Affecting Accounting Conservatism. Guided by: Nurita Affan and Ledy Setiawati. This research was conducted to examine whether leverage, company size, capital intensity, growth opportunities and litigation have an effect on accounting conservatism. This study uses secondary data obtained from financial statements of manufacturing companies in 2014-2017. Based on the purposive sampling method, there were 84 samples that fit the criteria. Samples This study used multiple linear regression analysis. The data obtained were analyzed using IBM SPSS Statistics 23. Software based on the results of tests conducted showed that: 1) The leverage ratio had a significant effect on the selection of accounting conservatism principles. 2) Company size has a significant effect on the selection of accounting conservatism principles. 3) capital intensity has a significant effect on the selection of accounting conservatism principles. 4) Chance of growth has a significant effect on the selection of accounting conservatism principles 5) Litigation costs have no significant effect on the selection of accounting conservatism principles.